Un país ignorado, un libro desconocido. Asturies, mitología e identidad - Blanco Martín, Carlos Javier (Nómadas. Critical Journal of Social and Juridical Science, 2011)
We offer a review of this book on Asturian mythology, La Creación del Mundo, y otros Mitos Asturianos where myths are exposed in Asturian folklore collected in the light of comparisons with Celtic mythology and other fields. Carrin exposes the survivals of an ancient European religion, widespread in the Atlantic area, but obscured by the Spanish obsession for all things around Latin and Mediterranean. Also provide clues about why asturianists largely ignore these critical issues